About some denominations for the umbilicus rupestris in the Galician-speaking territory: an analysis based on data from the ALGa (II) - Dourado Fernández, Rocío (Madrygal. Revista de Estudios Gallegos, 2013)
In this work we compiled several of the forms registered in the ALGa (Atlas Lingüístico Galego) to designate the plant which scientific name is Umbilicus rupestris (Salisb.) Dandy. From an index of more than fifty items, we elaborate proposal of grouping based on motivational and, to a lesser extent, etymological criteria. Likewise, we have always tried to contextualize the information obtained inside the Romanic area, where we have detected quidelines similar to those one we have been able to identify in the Galician-speaking territory.